2018
DOI: 10.3390/genes9090436
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Metagenomic Signals Recovered from Lyuba, a 42,000-Year-Old Permafrost-Preserved Woolly Mammoth Calf

Abstract: The reconstruction of ancient metagenomes from archaeological material, and their implication in human health and evolution, is one of the most recent advances in paleomicrobiological studies. However, as for all ancient DNA (aDNA) studies, environmental and laboratory contamination need to be specifically addressed. Here we attempted to reconstruct the tissue-specific metagenomes of a 42,000-year-old, permafrost-preserved woolly mammoth calf through shotgun high-throughput sequencing. We analyzed the taxonomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…A previous metagenome-based study revealed the presence of actinobacterial reads in different tissues of mammoth remains 35 . However, studying metagenome data always has the risk for misassembly of (damaged) DNA, which is not the case when isolates are grown up and then sequenced.…”
Section: Discussionmentioning
confidence: 97%
“…A previous metagenome-based study revealed the presence of actinobacterial reads in different tissues of mammoth remains 35 . However, studying metagenome data always has the risk for misassembly of (damaged) DNA, which is not the case when isolates are grown up and then sequenced.…”
Section: Discussionmentioning
confidence: 97%
“…We also attempted to use metagenome analysis to see if we could retrace the bacterial genome sequences in the intestinal metagenome and not in the surrounding ice. Previous studies on a mammoth microbiome showed that it is extremely difficult to get data of sufficient quality to ascertain the origin of microbes (Ferrari et al, 2018), and indeed we ran into similar issues, and the approach was abandoned. Finally, it is relevant to note that there are no records of scientists at our institute having previously worked with strains of the genera Oerskovia , Sanguibacter or Saccharopolyspora , nor are these known as common contaminants, which minimises the chance of laboratory contamination.…”
Section: Discussionmentioning
confidence: 99%
“…Modern contamination of ancient samples is typified by higher concentrations of DNA than the background of highly degraded endogenous genetic material (low coverage and depth). Ancient DNA is also highly fragmented, with a characteristic pattern of nucleotide modifications (Pääbo 1989; Dabney, Meyer, and Pääbo 2013; Skoglund et al 2014), even in frozen (Ravin, Prokhortchouk, and Skryabin 2015; Mardanov et al 2012; Ferrari et al 2018; Van Geel et al 2011) or fully desiccated (Hofreiter et al 2000; Karpinski, Mead, and Poinar 2017; Poinar et al 2003; Delsuc et al 2019; Wood et al 2013) specimens that tend to encourage DNA preservation.…”
Section: Methodsmentioning
confidence: 99%
“…Initially, these began with amplicon-based methods (Tito et al 2012; Hofreiter et al 2000) and permafrost specimens (Hagelberg, Hofreiter, and Keyser 2015; Mardanov et al 2012; Ravin, Prokhortchouk, and Skryabin 2015). More recently, shotgun metagenomics has been used to analyze all the DNA present within ancient samples without relying on PCR amplification, avoiding the associated biases, and giving a more accurate insight into the relative abundances of community members (McLaren, Willis, and Callahan 2019; Ferrari et al 2018; Durazzi et al 2021). Although shotgun metagenomics has been performed on ancient packrat ( Neotoma sp.)…”
Section: Introductionmentioning
confidence: 99%